Language Styles in The Song Lyrics of “Citra Cinta”, “Sifana”, “Less Salt”, and “Corona Virus” by Rhoma Irama - Amin Mujid Farihul (EDP Sciences, 2021)
This study aims to describe the language style contained in the lyrics of the song Citra Cinta, Sifana, Lack of Salt, and the Coronavirus by Rhoma Irama. The research data is in the form of song lyrics from the four songs. The method used in this study includes three strategic stages, namely the stage of data collection, data analysis, and presentation of the results of data analysis. The results showed that in the four-song lyrics which were used as the object of the study, there were language styles of the affirmation, comparison, and contradictory groups. The affirmation language style group includes parallelism, enumeration, pleonasm, repetition, climax, interruption, correction, and asidenton. For the comparative language style group, there are similes, litotes, metaphors, allusions, and groups of contradictory styles that have only one type, namely antithesis.